2007
DOI: 10.1037/0021-9010.92.5.1200
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling role perceptions: How perceived role breadth, discretion, instrumentality, and efficacy relate to helping and taking charge.

Abstract: The objective of this study was to empirically disentangle role perceptions related to organizational citizenship behavior (OCB) that have been confounded in past research, investigate their unique relationships with both an affiliative (helping) and a challenging (taking charge) form of OCB, and determine their relative importance in explaining these 2 forms of OCB. The authors also examined whether role discretion and role breadth independently moderate the procedural justice-to-OCB relationship. The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
297
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(328 citation statements)
references
References 90 publications
26
297
2
3
Order By: Relevance
“…Prior research has shown that role construals affect people's understandings of what helping is (Morrison, 1994;Van Dyne and LePine, 1998;McAllister et al, 2007), what constitutes adequate assistance (Coyle-Shapiro, 2002), or what kind of reciprocity helping should engender (Toegel, Kilduff, and Anand, 2013). Our findings go further to suggest that, even when parties agree that an episode should be considered "helping," the boundaries of helping roles must still be negotiated in order to clarify what norms and behaviors are applicable.…”
Section: Diagnostic (In)congruencesupporting
confidence: 46%
“…Prior research has shown that role construals affect people's understandings of what helping is (Morrison, 1994;Van Dyne and LePine, 1998;McAllister et al, 2007), what constitutes adequate assistance (Coyle-Shapiro, 2002), or what kind of reciprocity helping should engender (Toegel, Kilduff, and Anand, 2013). Our findings go further to suggest that, even when parties agree that an episode should be considered "helping," the boundaries of helping roles must still be negotiated in order to clarify what norms and behaviors are applicable.…”
Section: Diagnostic (In)congruencesupporting
confidence: 46%
“…McAllister, Kamdar, Morrison, and Turban (2007) showed individuals are more likely to take charge when they not only are high in role-breadth selfefficacy but also perceive their organization as high in procedural justice. Individuals are thus more likely to be proactive if they perceive proactive behaviors as a part of their roles (high role-breadth self-efficacy) and as such do not view these behaviors as too risky to engage in.…”
Section: Summary and Moderating Influencesmentioning
confidence: 99%
“…Indeed, people with high self-efficacy are more willing to engage in prosocial behaviors because they feel that their efforts will increase the likelihood they will genuinely help others (Bandura, 1977). Furthermore, past research suggests that employees high in self-efficacy engage in prosocial behaviors (McAllister, Kamdar, Morrison, & Turban, 2007). Interpersonal helping is positively associated with reputation and status and, ultimately, performance (Flynn, 2003).…”
Section: Moderators Of Envy's Effectsmentioning
confidence: 99%